The Influence of Gratitude on the Meaning of Life: The Mediating Effect of Family Function and Peer Relationship - Zhang, Ping; Ye, Lin; Fu, Fang; Zhang, Lan Ge (Frontiers in Psychology, 2021)
Objective: This study aims to explore the influence of gratitude on the meaning of life of college students and the mediating effect of family function and peer relationship. Methods: a total of 1049 college students (mean age 18.59 ± 0.96) were investigated by gratitude scale, family function scale, peer relationship questionnaire and meaning of life scale. Results: (1) gratitude was positively correlated with meaning existence (r = 0.39, P < 0.05) , meaning seeking (r = 0.23, P < 0.05) and peer relationship (r = 0.32, P < 0.05); meanwhile, it is also positively correlated with family function (r = 0.34, P < 0.05); (2) Family function partially mediates the relationship between gratitude and meaning of life. Similarly, peer relationship partially mediates the relationship between gratitude and meaning of life. Conclusion: the mediating model showed that grateful individuals can better sense the meaning of life by perceiving good family function and good peer relationship.